ROLE OF COMBINED KETOCONAZOLE AND TAMSULOSIN IN SUCCESSFUL TRIAL OF VOIDING WITHOUT CATHETER (TWOC) IN PATIENTS WITH ACUTE URINARY RETENTION DUE TO BENIGN PROSTATIC OBSTRUCTION - Asim, Muhammad; Ahmed, Syed Farhan; Ali, Muhammad Sajid; Memon, Imran; Memon, Waqas; Rashid, Muhammad; Abbas, Kiran; Ahmed, Moiz (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the frequency of patients with successful Trial of voiding without catheter (TWOC) after acute urinary retention secondary to benign prostatic hyperplasia in patients taking ketoconazole and tamsulosin vs tamsulosin alone. Study Design: A randomized controlled trial. Place and Duration: The current study was conducted at Urology Ward, Liaquat National Hospital, Pakistan for a period of six months. Methodology: A total of 162 patients presenting with acute urinary retention were divided into two groups. Group A received tamsulosin 0.4mg OD and ketoconazole 200mg while Group B received tamsulosin and placebo. Trial of voiding without a catheter was induced after one week of medication. SPSS version 20 was used for data compilation and analysis. Results: In Group-A, 85.2% of patients were able to void as compared to group B, where only 74.1% of patients were able to void (p<0.05). Successful trial of voiding without catheter was observed in 79.0% and 60.5% in patients of Group-A and Group-B respectively. The association of successful TWOC with the two study groups was found significant (p=0.010). Conclusion: TWOC in men catheterized for AUR due to BPH was significantly more successful if treated in a combination of ketoconazole and tamsulosin as compared to tamsulosin only.